2022
DOI: 10.1186/s12889-022-13445-w
|View full text |Cite
|
Sign up to set email alerts
|

Safe spaces for beneficiaries of a combination HIV prevention intervention for adolescent girls and young women in South Africa: access, feasibility, and acceptability

Abstract: Background Safe Spaces are a feature of combination HIV prevention interventions for adolescent girls and young women (AGYW) in South Africa. We investigated whether AGYW at risk for adverse sexual and reproductive health (SRH) outcomes accessed Safe Spaces that were part of an intervention, as well as their feasibility and acceptability. Methods In December 2020 to February 2021, as part of a process evaluation of a combination HIV prevention inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…Interestingly, the informal healthcare providers believed that their capacity to deliver more adolescent-friendly SRH services following the capacity-building intervention enabled increased patronage by adolescent clients. For the formal providers, an inference was that the introduction of safe spaces, extracurricular activities and games following the SRH training of health providers improved SRH service utilisation among adolescent clients, which was similar to findings from a study in South Africa, where 89.4% of adolescent girls and young women reported that the safe spaces for delivering adolescents’ SRH services offer a safe, quiet and comfortable environment when accessing the SRH services 38. This shows that the creation of safe spaces could reduce the unmet SRH needs of adolescents 38…”
Section: Discussionsupporting
confidence: 76%
“…Interestingly, the informal healthcare providers believed that their capacity to deliver more adolescent-friendly SRH services following the capacity-building intervention enabled increased patronage by adolescent clients. For the formal providers, an inference was that the introduction of safe spaces, extracurricular activities and games following the SRH training of health providers improved SRH service utilisation among adolescent clients, which was similar to findings from a study in South Africa, where 89.4% of adolescent girls and young women reported that the safe spaces for delivering adolescents’ SRH services offer a safe, quiet and comfortable environment when accessing the SRH services 38. This shows that the creation of safe spaces could reduce the unmet SRH needs of adolescents 38…”
Section: Discussionsupporting
confidence: 76%
“…On the other side, not everybody was able to adjust. Adolescent participants mentioned family commitments and chores as a barrier to program participation, as also identified in other studies [ 53 , 54 ]. Another facilitator to program attendance was the provision of incentives in the form of transport refunds and lunch/snacks.…”
Section: Discussionsupporting
confidence: 63%
“…Another facilitator to program attendance was the provision of incentives in the form of transport refunds and lunch/snacks. Transportation costs are widely discussed as a barrier to program participation [ 53 , 55 ] as they can be prohibitive for already resource-limited families. In fact, some participants mentioned struggling with transportation costs despite the refund as they had to pay for transport upfront.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Binary and categorical variables relating to socio-demographics, COVID-19 testing and outcomes, as well as potential barriers to, and facilitators of COVID-19 vaccination were created from survey questions and are described in Table 1. A cluster variable with two categories (relatively low and relatively high) was created for socio-economic status (SES) using 13 SES-related variables included in the survey [30]:…”
Section: Methodsmentioning
confidence: 99%